Impact of Professionally Important Qualities of Patrol Police Officers on Decision-making Strategies - Pomytkina Liubov; Pomytkin Eduard; Yakovytska Lada (Insight: the psychological dimensions of society, 2024)
The article presents the results of a theoretical-empirical research of the impact of professionally important qualities of employees on decision-making strategies in the activity of the patrol police; at the theoretical level, the achievements of modern scientists and practitioners regarding the specifics of decision-making in extreme conditions of activity have been analyzed; the data on the specifics of patrol police activity in the conditions of military operations were clarified. The aim of the study is to highlight the research findings on the impact of professionally important qualities of patrol police officers on their decision-making strategies in the professional activity. Research methods: “Assessment of operational visual memory” (Münsterberg, 2011), “Diagnosis of attention selectivity” (Münsterberg, 2011); “Research on the level of impulsivity” by V. Losenkov (Lemak & Petryshche, 2012); “Diagnosis of communicative social competence” (Fetiskin et al., 2002); “Melbourne Decision-Making Questionnaire” (Mann et. al., 1997). The results. It was found that the constructive decision-making strategy “vigilance” is determined by such dominant characteristics as emotional stability, independence, rationality, attention selectivity and purposefulness. Thus, for patrol officers, who are characterized by high emotional stability, independence, rationality, purposefulness, as well as a high level of attention selectivity, “vigilance” will be a characteristic strategy, that is, a rational strategy. Regarding non-constructive decision-making strategies, which, unfortunately, take place among patrol police officers, the results are as follows: the “avoidance” strategy is determined by sensuality, emotionality, which hinders the ability to solve problems and make decisions independently; the choice of the “procrastination” strategy is influenced by the impulsivity indicator; the “hypervigilance” strategy is influenced by such characteristics as inattention and impulsiveness of thinking. Discussion and conclusions. It was substantiated that the choice of decision-making strategies in the work of the patrol police is influenced by the level of development of employees’ professionally important qualities; the obtained data must be taken into account during the formation of patrol police teams, as well as in the training and retraining of employees. This approach will ensure a conscious choice of constructive strategies and increase the effectiveness of activities.